Le creuset et l'orfèvre : le parcours d'Ahmad Amîn (1886-1954) - Emmanuelle Perrin (Revue des Mondes Musulmans et de la Méditerranée)
An important figure in Egypt during the first half of the 20th century, Ahmad Amîn (1886-1956) belongs to the generation of thinkers and writers who dominated the intellectual and literary life of the period between the Two World Wars. As he refers to in his autobiography, Hayâtî, his itinerary and literary output offers an illustration of the experience, the projects and the questions encountered by intellectuals who lived at the end of the reformist movement (islâh) and the cultural revival of the Nahda. The figure of the intellectual as a mediator, who embodies the authority of knowledge and the talent of communication, insisting upon the expansion of instruction as an instrument of social progress, is present throughout his numerous works. Ahmad Amîn envisioned the role of the reformers similar to the work of a goldsmith who composes an alloyage : in order to reduce differences between mentalities, one must melt them and then mix them in a single recipient.